Creencias Frente a Las Agresiones Sexuales Construidas Por Los Usuarios y Usuarias Del Transporte Masivo De Bogota (2016)
In this research the beliefs and users have the mass transit from sexual assault is. Using qualitative methodology, and through semi-structured interview was possible to identify categories like information, experiences and reactions and mass transit users to events of sexual assault. As relevant results, we can highlight the lack of a clear conceptualization of what defines sexual assault, finding differences between the beliefs that men and women; the first attribute greater importance to direct aggression (touching) and the latter believe that all behavior is sexual assault (touching, looks, thoughts and compliments); well within the state of art data legally they support the punishment of offenders but not materialize for lack of evidence, since sexual aggression leaves no palpable sequel were found. Finally it was noted that for both men and women the only aggressor is the man and this same not contemplate the possibility of becoming a victim.